INTEGRASI NILAI AGAMA DALAM KURIKULUM PENDIDIKAN FORMAL DI INDONESIA: KAJIAN KONSEPTUAL DAN PRAKTIK DI LEMBAGA PENDIDIKAN - Tomia, Enda; Nur Ahid; Eva Fauziah (Atta'dib Jurnal Pendidikan Agama Islam, 2025)
This study analyzes the development of religious education curricula in three educational settings in Indonesia: Islamic boarding schools, schools, and madrasahs. The curriculum is positioned as a strategic instrument in shaping students’ religious character and adaptive capacity in facing contemporary challenges. This research employs a qualitative descriptive approach through a literature study to examine curriculum models, principles, and implementation strategies tailored to the characteristics of each institution. The findings indicate that Islamic boarding schools emphasize preserving classical Islamic scholarship, moral education, and spiritual formation. Schools integrate religious values into the national curriculum through modern pedagogical approaches, while madrasahs apply an integrated model that combines religious and general education with a greater focus on religious subjects. In addition, curriculum contextualization, digital integration, and the implementation of religious moderation values are identified as the main innovations and challenges. These results highlight that curriculum development in these three institutions significantly contributes to shaping a generation that is academically competent, morally grounded, and able to play a constructive role in society.